HUBUNGAN PENGETAHUAN IBU DENGAN CARA MENYUSUI YANG BENAR PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS MUARA BUNGO I KABUPATEN BUNGO TAHUN 2017 - Hardiana Hardiana (Universitas Batanghari Jambi, 2018)
Following the World Health Organization (WHO) report in 2015, the Infant Mortality Rate (IMR) in the world was 33.6 per 1000 live births (WHO, 2016). Exclusive breastfeeding in the working area of Muara Bungo I Health Center is still low. Number of 0-6 months infants in the data were 46 babies, with they’re who given exclusive breastfeeding as many as 25 (50.7%). This research is analytical survey with cross sectional approach using total sampling method with 46 respondents using primary data in the working area of Muara Bungo I Health Center in 2017. Majority of respondents who had knowledge were 28 respondents (60.9%) and who had wrong feeding method as many as 27 respondents (58.7%). And P value = 0.000 (P value <0.05) means there is a relationship between knowledge by the right way of breastfeeding in the working area of Muara Bungo I Health Center in 2017.Keywords : Knowledge, Right Way of Breast Feeding